Penerapan Manajemen Risiko Pada PT. Mayora Indah Tbk Dengan Metode Iso 31000:2018 - Fauziah Elna Novita Sari; Nefri Rahmadani; Nana Putri; Wildatun Hasanah (Universitas Islam Negeri Mahmud Yunus Batusangkar, 2023)
The purpose of this study was to determine the application of risk at PT Mayora Tbk. The research method uses a qualitative approach. Data collection techniques using documentation through literature review and interviews. The results showed that the risk management system in the company has been implemented using the principle of caution by considering short-term and long-term risks, this is used for the sake of continuity and development of the company's performance, so this is the right type of risk, namely speculative risk, to minimize a risk event that occurs in the company, it is applied with the ISOO 31000 2018 method. The existence of various risks faced then has an impact on PT Mayora Indah Tbk. The occurrence of speculative risk that is being experienced by the company, therefore residual risk is needed so that the risks that occur can reduce the risks that occur in the company